Where Have All the T Cells Gone? - Velia, Gerlanda (Immunity, 2018)
Glioblastoma are highly immunosuppressive brain tumors that are known for their T cell paucity. In a recent issue of Nature Medicine, Chongsathidkiet et al. (2018) discovered a brain-specific mechanism of tumors to escape immunosurveillance by trapping T cells in the bone marrow through the loss of sphingosine-1-phosphate (S1P) receptor on the T cell surface.